The Idea of Arabic Influence Patterns in the Indonesian and Malay Languages - Haji Harun, Makmur; Arifai, Ahmad; Hasan, Nur (EDUCATE : Journal of Education and Culture, 2024)
Arabic is absorbed into many other languages in the world, especially the majority of the Muslim population, and then melted into a speech language as a means of communication. Various Arabic terms are used in the communication of the high literary touches in accordance with the oral narrative including in Indonesia and Malaysia in particular and in Southeast Asia generally. The development of language in these two countries continues to expand its use so that it is no longer merely as an intermediate language but also the absorption of language used through literature, science, media, literature, Law, economics, social, art, Other cultures as the appreciation of the civilization of the local Islamic community, as well as its pattern, symbol and philosophy of life. There are many Arab removals that are entered and used in Bahasa Indonesia and Malay using certain patterns to facilitate the user to speak verbally and written. The purpose of this study aims to analyze the pattern of absorption of Arabic into Indonesian and Malay language in communicating as a fundamental proof of foreign uptake that underlies the height of philosophy and literature. The methodology of the study used is also developed through a library study with various forms of methods, theories and patterns as an easy channel to understand more fundamentally the form of theory and accounting.